Public Health Palliative Care and Public Palliative Care Education (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The collection on “Public Health Palliative Care (PHPC) and Public Palliative Care Education (PPCE)” highlights recent advances and challenges in PHPC and PPCE. The articles demonstrate the breadth and diversity of local responses from across the globe, including Europe, Asia, Australia and South America. The COVID-19 pandemic clearly shows how collaboration between healthcare services and communities is an essential component of public health. The collection adds to the growing body of knowledge, based on practice, theory and research, about PHPC and PPCE. It is clear that global perspectives of PHPC are best expressed through both international, national and local activities including PPCE, such as Last Aid. Partnerships between healthcare services, civic organisations and communities are essential to increase awareness, skills and practice. It is evident that PHPC and PPCE are needed to improve palliative care support by the public in communities. These examples show that encouraging work on this important theme is ongoing worldwide, although more effort for implementation and research is needed.